The Effect of Discipline and Occupational Health Safety (K3) on Employee Performance at PT. Indo Farma Pharmaceutical Production Unit Jakarta - Taufiqqurachman; Noor Permadi; Noor Muhammadi (Institute of Computer Science (IOCS), 2021)
This study aims to determine and analyze the effect of discipline and Occupational Health and Safety (K3) partially and simultaneously on employee performance at PT. Indo Farma Pharmaceutical Production Unit Jakarta. The approach used in this research is quantitative research and the strategy used in this research is the associative strategy. The research method that will be used is descriptive analysis method using regression analysis, namely to determine how much the contribution / influence of discipline and occupational health and safety (K3) to the performance of employees at PT. Indo Farma Pharmaceutical Production Unit Jakarta. In this study, data processing was carried out using SPSS ver. 24.00. The population in this study were all employees of PT. Indo Farma Jakarta Pharmacy Production Unit, amounting to 52 people. The sample used is based on sensory techniques as many as 52 employees at PT. Indo Farma Jakarta Pharmacy Production Unit. Based on the analysis and discussion, it shows that discipline has a significant positive effect on employee performance at PT. Indo Farma Pharmacy Production Unit Jakarta, it can be seen that a significant value of 0.000 <0.05, the first hypothesis (H1) is accepted; Occupational Health Safety (K3) has a significant positive effect on employee performance at PT. Indo Farma Jakarta Pharmacy Production Unit, it can be seen that a significant value of 0.044 <0.05, the second hypothesis (H2) is accepted and simultaneously discipline and Occupational Health Safety (K3) have a significant positive effect on employee performance at PT. Indo Farma Jakarta Pharmacy Production Unit with a significant value of 0.000 <0.05, the third hypothesis (H3) is accepted.